Aktivitas Antibakteri Sediaan Microneedle Acne Patch Ekstrak Etanol Daun Belimbing Wuluh (Averrhoa bilimbi Linn) terhadap Staphylococcus epidermidis - Fitriana, Mia; Sarwo, Laura; Wathan, Nashrul (Universitas Borneo Lestari, 2025)
Acne is often accompanied by inflammation and triggers antibacterial activity such as S. Epidermidis. A. Bilimbi folium are known to inhibit the growth of S. Epidermidis. Microneedle (MN) is a preparation with small needles measuring 50-900 μm that can be applied to deliver active ingredients for acne treatment. The effect of concentration of A. Bilimbi MN acne patch leaf extract can cause changes in antibacterial activity. The purpose of this study was to determine the effect of the concentration of ethanol extract of A. Bilimbi folium on MN acne patch preparation on the inhibition of S. Epidermidis. The research was conducted by making 5 MN formulas with different extract concentrations and then testing the antibacterial activity with agar diffusion method. The negative control used was the formula without extracts while the positive control used chloramphenicol and acne patch preparation on the market. The results showed the clear zone of F1 (1%), F2 (5%), F3 (10%), F4 (15%), F5 (20%) of 1.86±0.485 mm; 3.15±0.556 mm; 5±0.526 mm; 8.25±0.687 mm; 9.43±0.809 mm, respectively. The conclusion of this study is that there was an effect of the concentration of ethanol extract of A. Bilimbi folium in the preparation of microneedle acne patches on the antibacterial activity of S. Epidermidis.